2023
DOI: 10.3389/fcell.2023.1130058
|View full text |Cite
|
Sign up to set email alerts
|

The Usher syndrome 1C protein harmonin regulates canonical Wnt signaling

Abstract: Human Usher syndrome (USH) is the most common form of hereditary combined deaf-blindness. USH is a complex genetic disorder, and the pathomechanisms underlying the disease are far from being understood, especially in the eye and retina. The USH1C gene encodes the scaffold protein harmonin which organizes protein networks due to binary interactions with other proteins, such as all USH proteins. Interestingly, only the retina and inner ear show a disease-related phenotype, although USH1C/harmonin is almost ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…One of the genes that are added to the network is USH1C. This gene was identified to play a role in hearing and vision ( 90 ), but the observation that it is highly co-expressed with the genes in the subnetwork, and the observation that mice with this gene knocked out display a decrease in circulating insulin levels, suggest that it is likely also playing an important role in diabetes. Vision impairments are a known phenotype of type 2 diabetes, and USH1C function is likely involved.…”
Section: Resultsmentioning
confidence: 99%
“…One of the genes that are added to the network is USH1C. This gene was identified to play a role in hearing and vision ( 90 ), but the observation that it is highly co-expressed with the genes in the subnetwork, and the observation that mice with this gene knocked out display a decrease in circulating insulin levels, suggest that it is likely also playing an important role in diabetes. Vision impairments are a known phenotype of type 2 diabetes, and USH1C function is likely involved.…”
Section: Resultsmentioning
confidence: 99%
“…USH type 1 (USH1) causes congenital deafness, vestibular defects, and early-onset RP, and the ush1c gene is involved in USH1. Schäfer et al (2023) demonstrated that one protein encoded by ush1c, the scaffold protein harmonin, interacts with coactivator β-catenin and suppresses the cWnt pathway, an important cell-cell communication pathway [98].…”
Section: Genetic Backgroundmentioning
confidence: 99%